Refugee Higher Education & Participatory Action Research Methods: Lessons Learned From the Field - Yanay, Hadas; Battle, Juan (Radical Teacher, 2021)
Refugee access to higher education is devastatingly low. Recognizing the complex barriers facing refugee learners, global educational initiatives are innovating flexible learning models which promote blended online and in-person learning modalities. This article describes the implementation of a five month, online-based internship pilot offered to 21 refugee participants in qualitative and quantitative research methods, through a participatory action research (PAR) framework in five different countries – Malawi, Kenya, South Africa, Rwanda, and Lebanon. The internship is part of the Global Education Movement (GEM), which brings refugees accredited online college degree and career development opportunities. Through direct engagement, observation of the internship and feedback from staff and participants, we highlight the ways in which the PAR model can serve as a dynamic learning approach to engage refugees in research practice and an evaluative tool of the GEM program. While the use of online learning presented several clear advantages, such as engaging multiple GEM sites simultaneously or insulating students from delayed studies due to the Coronavirus pandemic, it also revealed variations in student competencies across program sites. In this article, we review the GEM PAR internship, its lessons learned and propose recommendations for future programming.